Quality by Design Approach in Pharmaceutical - Waghmare Rohit,; Bharatee Chaudhari, (Asian Journal of Pharmaceutical Research and Development, 2026)
This review aims to clarify the concept of Pharmaceutical Quality by Design and delineate its foundational objectives within the context of drug development and manufacturing. It traces the evolution from traditional quality control, which relied heavily on post-production testing, to the proactive and integrated approach of QbD, emphasizing quality built in at every stage. This systematic approach begins with predefined objectives and prioritizes comprehensive product and process understanding, coupled with robust process control strategies, all underpinned by sound scientific principles and rigorous quality risk management . This transformative methodology ensures that quality is not merely tested into the product but is systematically designed and built-in from the outset, leading to enhanced product quality and reduced batch-to-batch variability. This review will delve into the seven vital elements of QbD, as outlined by the International Council for Harmonization guidelines Q8, Q9, and Q10, examining their interplay in achieving a robust control strategy and ultimately a Quality Target Product Profile. Furthermore, this article will explore the practical implementation of QbD, addressing its complexities and showcasing its applications across various pharmaceutical development stages. By moving beyond traditional trial-and-error methods, QbD fosters a science-based and risk-oriented strategy that optimizes drug product formulation and manufacturing processes. This methodical approach mandates the initial establishment of a Quality Target Product Profile and the subsequent identification of Critical Quality Attributes derived directly from these objectives, thereby guiding the entire development process.